Moderasi Beragama Berbasis Humanisme Religius untuk Menyikapi Politik Identitas bagi Mahasantri di Perguruan Tinggi Pesantren Jember - Faisol, Noga Riza (DIMAR: Jurnal Pendidikan Islam, 2024)
Pondok Pesantren (PP) is the first traditional Islamic educational institution in Indonesia. In the run-up to elections, PP often becomes a political commodity and a target planted to get votes and have a boarding school, where many students live in Islamic boarding schools (mahasantri). The focus of this research is how to internalize the values of religious moderation based on religious humanism in responding to identity politics for students of the IAI Al-Qodiri Jember Islamic Education Study Program? And to describe the focus of the research, the researcher used a qualitative research method with a phenomenological approach, Porposive Sampling was used to determine informants and data analysis used interpretive phenomenological analysis (IPA). From the use of the above method, the research results show that: Internalization of religious moderation values based on religious humanism in responding to identity politics for students of the IAI Al-Qodiri Jember Islamic Religious Education Study Program through 1) vision and mission, 2) curriculum and 3) interaction social.